7. PERAN TEKNOLOGI INFORMASI DALAM MENCIPTAKAN MASYARAKAT INFORMASI - Farida, Naili (Faculty of Social and Political Sciences Diponegoro University, 2009)
Growth of fast information technology have important casting in aspect of life of public. Information technology have impact at life of public. Information technology current without desisting to start from internet. So, nirkable until telephone system, digital cable continually alter way of traditional communications become modern. Role of information technology can create and have an in with information society available for using internet for : education, business, consumer, health, telecommunications, seluler, agriculture, mass media, service, internet, travel and is govermental. Important other factor is ethics, political and social so that information technology is not misused for the sake of criminals and give protection to individual or organizational and public to rights which owned and rule of law from government to be able to protect importance of public.